1998
DOI: 10.1103/physrevlett.81.1306
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Resonant Photoemission in Gd

Abstract: The phenomenon of resonant photoemission happens when, in addition to a direct photoemission channel, a second indirect channel opens up as the absorption threshold of a core level is crossed. A massive increase in emission cross section can occur, but the nature of the process remains clouded. Using novel magnetic linear dichroism in photoelectron spectroscopy experiments and theoretical calculations, we can now clearly demonstrate that temporal matching of the processes as well as energy matching is a requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
19
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…In IPES, a very different set of Problem." Thus, because of the unique constraints placed upon RIPES owing to its quantum-mechanical nature [26,27] and the availability of a recently verified model of the complex internal structure of the unoccupied density of states (UDOS) of uranium dioxide involving both U5f and U6d states [16], it will be shown that the main and satellite peaks in the RIPES correspond to the 5f and 6d thresholds of the unoccupied DOS. This result opens the door to application of this approach to the more radioactive actinides and the isolation of their 5f and 6d components in the UDOS.…”
mentioning
confidence: 99%
“…In IPES, a very different set of Problem." Thus, because of the unique constraints placed upon RIPES owing to its quantum-mechanical nature [26,27] and the availability of a recently verified model of the complex internal structure of the unoccupied density of states (UDOS) of uranium dioxide involving both U5f and U6d states [16], it will be shown that the main and satellite peaks in the RIPES correspond to the 5f and 6d thresholds of the unoccupied DOS. This result opens the door to application of this approach to the more radioactive actinides and the isolation of their 5f and 6d components in the UDOS.…”
mentioning
confidence: 99%
“…The huge experimental output from RPES on correlated materials [7,[11][12][13][14][15][16] and the intriguing quest for a determination of local magnetic properties put forward by pioneering experiments [14][15][16] call for advancements in the theoretical description of this spectroscopy. In experiments on CuO and Ni, it was shown that the RPES photocurrent with circular polarized light is spin polarized in antiferromagnets [14,15] and Curie paramagnets [16].…”
mentioning
confidence: 99%
“…However, second order processes, like resonant inelastic X-ray scattering (RIXS) and resonant photoemission (RPES), remain a major challenge for theory. For RPES, existing approaches are semiempirical [7][8][9][10], based on a well defined two-holes final state and on small clusters, and thus do not take into account the delocalization of intermediate states, the bandstructure of the system and multiple scattering effects in the propagation of photoelectrons.The huge experimental output from RPES on correlated materials [7,[11][12][13][14][15][16] and the intriguing quest for a determination of local magnetic properties put forward by pioneering experiments [14][15][16] call for advancements in the theoretical description of this spectroscopy. In experiments on CuO and Ni, it was shown that the RPES photocurrent with circular polarized light is spin polarized in antiferromagnets [14,15] and Curie paramagnets [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prepeak structure remains as individual peaks but at higher photon energies, where the outgoing electron can actually escape, coupling to the continuum states generates a large, broad peak, that is referred to as the giant resonance. 24 The prepeaks are of atomic character, and thus, in Ce are rather insensitive to the phase of the metal. Only in ␣-Ce is a slight broadening of the pre-peaks observed due to d-f hybridization.…”
mentioning
confidence: 99%